Implementing exercise in cancer care: study protocol to evaluate a community-based exercise program for people with cancer. Issue 1 (December 2017) - Cormie, Prue; Lamb, Stephanie; Newton, Robert; Valentine, Lani; McKiernan, Sandy; Spry, Nigel; Joseph, David; Taaffe, Dennis; Doran, Christopher; Galvão, Daniel
Abstract Background Clinical research has established the efficacy of exercise in reducing treatment-related side-effects and increasing wellbeing in people with cancer. Major oncology organisations have identified the importance of incorporating exercise in comprehensive cancer care but information regarding effective approaches to translating evidence into practice is lacking. This paper describes the implementation of a community-based exercise program for people with cancer and the protocol for program evaluation. Methods/Design The Life Now Exercise program is a community-based exercise intervention designed to mitigate and rehabilitate the adverse effects of cancer and its treatment and improve physical and psychosocial wellbeing in people with cancer. Involvement in the program is open to people with any diagnosis of cancer who are currently receiving treatment or within 2 years of completing treatment. The 3-month intervention consists of twice weekly group-based exercise sessions administered in community exercise clinics under the supervision of exercise physiologists trained to deliver the program. Evaluation of the program involves measures of uptake, safety, adherence and effectiveness (including cost effectiveness) as assessed at the completion of the program and 6 months follow-up. Discussion To bridge the gap between research and practice, the Life Now Exercise program was designed and implemented to provide people with cancer access to evidence-based exercise medicine. The framework for program implementation and evaluation offers insight into the development of feasible, generalizable and sustainable supportive care services involving exercise. Community-based exercise programs specifically designed for people with cancer are necessary to facilitate adherence to international guidelines advising patients to participate in high-quality exercise. Trial Registration ACTRN12616001669482 (retrospectively registered 5 Dec 2016).